Development of Teaching Materials for Dual Visual Work Assessment Parameters : P-Books and E-Books in the Department of Fine Arts - Adek Cerah Kurnia Azis; Sugito Sugito; Gamal Kartono; Mesra Mesra; Nelson Tarigan; Hadi Alhail; Vivi Destri Yumielda (Jurnal Kependidikan)
This study aims to develop assessment-focused teaching materials for dual-dimensional visual works in the form of valid, practical, and effective p-books and e-books for the Department of Fine Arts. Employing the R&D method with the 4D model (define, design, develop, and disseminate), the research used a Likert scale questionnaire as the instrument, with data analysis techniques covering validity, practicality, and effectiveness assessments. The study results indicated that the teaching materials, both p-books and e-books, were highly valid with an average score of 87.8%. Furthermore, these materials proved to be highly practical for students in Shape Drawing, Illustration Drawing, Visual Communication Design (DKV), Graphic Arts, and Sketching courses, with a practicality score of 84.16%. They were also deemed effective, as students’ activities (such as reading modules, asking and answering questions, and completing assignments) resulted in an effectiveness score of 85.41%. Thus, the teaching materials are confirmed to be valid, practical, and effective for application in the specified Fine Arts courses.